2020
DOI: 10.1563/aaid-joi-d-20-00302
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics for the Treatment of Peri-Implant Mucositis in Patients With and Without Type 2 Diabetes Mellitus

Abstract: The hypothesis was that probiotic therapy (PT) does not offer additional benefits to mechanical debridement (MD) for treatment of diabetic subjects with peri-implant mucositis (PM). This study compared the influence of PT as an adjunct to MD for the treatment of PM in type2 diabetic and non-diabetic patients over a 12-month follow-up period. Patients with and without type-2 diabetes were encompassed. Based upon treatment-procedure, PM patients were categorized into 2 groups: (a) Non-surgical + PT; and (b) Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Clinical studies have compared the effects of mechanical plaque removal alone or in combination with local application of Limosilactobacillus reuteri in the treatment of peri-implant diseases. The results showed that patients who received probiotic supplementation showed better improvements in clinical parameters such as probing bleeding and probing depth, regardless of the extent of the disease [ 208 , 211 ]. Butera et al suggested that the use of Limosilactobacillus reuteri , Lactobacillus brevis, or Lactiplantibacillus plantarum in the treatment of peri-implant diseases led to varying degrees of improvement in clinical indices such as bleeding on probing, attachment loss, and plaque index [ 212 ].…”
Section: The Role Of Probiotics Against Peri-implant Diseasesmentioning
confidence: 99%
“…Clinical studies have compared the effects of mechanical plaque removal alone or in combination with local application of Limosilactobacillus reuteri in the treatment of peri-implant diseases. The results showed that patients who received probiotic supplementation showed better improvements in clinical parameters such as probing bleeding and probing depth, regardless of the extent of the disease [ 208 , 211 ]. Butera et al suggested that the use of Limosilactobacillus reuteri , Lactobacillus brevis, or Lactiplantibacillus plantarum in the treatment of peri-implant diseases led to varying degrees of improvement in clinical indices such as bleeding on probing, attachment loss, and plaque index [ 212 ].…”
Section: The Role Of Probiotics Against Peri-implant Diseasesmentioning
confidence: 99%
“…Of the RCTs, five studies [8,10,11,19,21] included periodontally healthy patients, one study [18] included edentulous patients, two studies [9,23] did not report any previous periodontal diagnostic information, and one study [22] included patients with a history of chronic periodontitis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…They have been extensively studied for their potential to improve intestinal health and stimulate the immune system [6]. However, there is a growing body of evidence [7][8][9][10] suggesting that probiotics may also be beneficial in the treatment of peri-implant mucositis. Probiotics containing Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Mucositis is a prevalent and harmful illness. Its prevalence during standard chemotherapy is between 20 and 40%, and it may reach 80% in individuals undergoing high-dose chemotherapy (such as a conditioning regimen for hematopoietic stem cell transplantation or HSCT) [9]. Approximately 60% of patients who experience it use mammalian targets of rapamycin Pharmaceuticals 2023, 16, 654 2 of 13 inhibitors such as everolimus and temsirolimus.…”
Section: Introductionmentioning
confidence: 99%